Testosterone deficiency and replacement: Myths and realities - Grober, Ethan D. (Canadian Urological Association Journal, 2014)
Testosterone deficiency, or hypogonadism, is common and may have deleterious effects on men, including decreased overall wellbeing, reduced sexual function and bone loss. Despite data demonstrating strong links between testosterone deficiency and significant comorbid conditions including type 2 diabetes and metabolic syndrome as well as the health benefits of testosterone-replacement therapy (TRT), some physicians are still hesitant to initiate these therapies, based on a number of prevailing myths associating TRT with adverse prostate health and recent concerns highlighting the possibility of increased cardiovascular risk.